ETHNOSCIENCE STUDY OF SHRIMP PASTE AT THE MERANTI ISLANDS AS A REPRESENTATION OF CHEMISTRY LEARNING - Siti Nazhifah; Maria Erna; Putri Adita Wulandari; Nabila Afifah Azuga (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2025)
This study explores the integration of ethnoscience into chemistry education by using the traditional shrimp paste production process in Meranti Islands Regency, Riau, Indonesia as a contextual learning resource. The research method used a qualitative descriptive case study approach, with data collection involving field observations, in-depth interviews with five shrimp paste producers (ethnographic data), and a review of scientific literature (scientific data). The findings indicate that the shrimp paste production process still heavily relies on inherited local knowledge and involves several stages: sorting and washing, crushing, molding, fermentation, drying, and heating over a fire. Each of these stages contains chemical aspects that can be analyzed through various approaches: a macroscopic approach (examining physical and chemical changes such as color, aroma, and texture), a submicroscopic approach (focusing on molecular and enzymatic interactions), and a symbolic approach (exploring chemical reactions such as hydrolysis, fermentation, and Maillard reactions). Furthermore, the study reveals that the community’s knowledge of the shrimp paste production process is supported by scientific principles, as documented in the literature. The results suggest that shrimp paste production not only contributes to the local economy and cultural preservation but also holds significant potential for enhancing students’ scientific literacy through an integrated chemical representation approach. The integration of these three levels of chemical representation is expected to provide students with a holistic and applied understanding of chemical concepts.